Polymeric nanoparticle-based mRNA vaccine is protective against influenza virus infection in ferrets - Gijs Hardenberg; Chantal Brouwer; Rachelle van Gemerden; Nicola J. Jones; Anthony C. Marriott; Jaap Rip (Elsevier, 2024)
New therapies and vaccines based on nucleic acids combined with an efficient nanoparticle delivery vehicle have a broad applicability for different disease indications. An alternative delivery technology for the successfully applied lipid nanoparticles in mRNA SARS-CoV-2 vaccines are nanoparticles composed of biodegradable poly(amido)amine-based polymers with mRNA payload. To show that these polymeric nanoparticles can efficiently deliver influenza hemagglutinin mRNA to target tissues and elicit protective immune responses, a relevant ferret influenza challenge model was used. In this model, our nanoparticle-based vaccine elicited strong humoral and cellular immune responses in the absence of local and systemic reactogenicity. Upon virus challenge, vaccinated animals exhibited reduced clinical signs and virus load relative to unvaccinated control animals. Based on these findings, further investigation of the polymeric nanoparticles in the context of prophylactic vaccination is warranted. Future studies will focus on optimizing the payload, the nanoparticle stability, the efficacy in the context of pre-existing immunity, and the applicability of the technology to prevent other infectious diseases.